Serotonergic Modulation of Sensory Neuron Activity and Behavior in Apteronotus albifrons - Marquez, Mariana M.; Chacron, Maurice J. (Frontiers in Integrative Neuroscience, 2020)
Organisms must constantly adapt to changes in their environment in order to survive. It is thought that neuromodulators such as serotonin enable sensory neurons to better process input encountered during different behavioral contexts. Here, we investigated how serotonergic innervation affects neural and behavioral responses to behaviorally relevant envelope stimuli in the weakly electric fish species Apteronotus albifrons. Under baseline conditions, we found that exogenous serotonin application within the electrosensory lateral line lobe increased sensory neuron excitability, thereby promoting burst firing. We found that serotonin enhanced the responses to envelope stimuli of pyramidal cells within the lateral segment of the electrosensory lateral line lobe (ELL) by increasing sensitivity, with the increase more pronounced for stimuli with higher temporal frequencies (i.e., > 0.2 Hz). Such increases in neural sensitivity were due to increased burst firing. At the organismal level, bilateral serotonin application within the ELL lateral segment enhanced behavioral responses to sensory input through increases in sensitivity. Similar to what was observed for neural responses, increases in behavioral sensitivity were more pronounced for higher (i.e., > 0.2 Hz) temporal frequencies. Surprisingly, comparison between our results and previous ones obtained in the closely related species A. leptorhynchus revealed that, while serotonin application gave rise to similar effects on neural excitability and responses to sensory input, serotonin application also gave rise to marked differences in behavior. Specifically, behavioral responses in A. leptorhynchus were increased primarily for lower (i.e.,  0.2 Hz) rather than for higher temporal frequencies. Thus, our results strongly suggest that there are marked differences in how sensory neural responses are processed downstream to give rise to behavior across both species. This is despite the fact that previous results have shown that the behavioral responses of both species to envelope stimuli were identical when serotonin is not applied.